2020
DOI: 10.1101/2020.04.30.20086926
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Depression, Anxiety and Depression-anxiety comorbidity amid COVID-19 Pandemic: An online survey conducted during lockdown in Nepal

Abstract: 29

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
60
8
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 16 publications
18
60
8
2
Order By: Relevance
“…This study examined the status of anxiety, depression and insomnia symptoms among health workers in Nepal during the early phase of the COVID19 pandemic. The prevalence of anxiety (41.9%) and depression (37.5%) symptoms among health workers in this study was higher than those found in a recent study conducted among the general population during COVID-19 pandemic in Nepal, which showed that 31% of respondents reported anxiety and 34% of respondents reported depression [30]. This might be because health workers have a higher risk of acquiring COVID-19 infection in comparison to the general population, and also due to the stressful and demanding nature of the job.…”
Section: Discussioncontrasting
confidence: 87%
“…This study examined the status of anxiety, depression and insomnia symptoms among health workers in Nepal during the early phase of the COVID19 pandemic. The prevalence of anxiety (41.9%) and depression (37.5%) symptoms among health workers in this study was higher than those found in a recent study conducted among the general population during COVID-19 pandemic in Nepal, which showed that 31% of respondents reported anxiety and 34% of respondents reported depression [30]. This might be because health workers have a higher risk of acquiring COVID-19 infection in comparison to the general population, and also due to the stressful and demanding nature of the job.…”
Section: Discussioncontrasting
confidence: 87%
“…About two-fth (37.2%) of the participants in this study reported high level of anxiety, a nding which is consistent with the 37.4% prevalence of anxiety found among high school students in China (Zhou et al, 2020) and 32.1% among a Nepalese population (Sigdel et al, 2020). This nding is, however, higher than the 28% obtained among Indian adults (Verma & Mishra, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Female participants, single living, and health professionals have higher risk of developing psychological impact during the COVID-19 pandemic [5]. Study in China showed significant differences in psychological distress among different population demographics and epidemiological characteristics of disease [9].…”
Section: Discussionmentioning
confidence: 99%
“…A high prevalence of psychological distress is noted in health professional from developing as well as developed countries [5,15]. A poorly governed healthcare system can incite more detrimental mental and physical health impact among frontline line health professionals [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation